Er: YAG laser-assisted minimally invasive non-surgical technique (MINST) for periodontal regeneration of maxillary canine teeth in dogs - Okano, Kimiyoshi (Frontiers in Veterinary Science, 2026)
Periodontal regeneration around maxillary canine teeth in dogs remains challenging because of limited surgical access and the risk of postoperative complications associated with flap surgery. This article presents a minimally invasive, flapless protocol for periodontal regeneration using an Er: YAG laser-assisted minimally invasive non-surgical technique (MINST). The method enables efficient removal of granulation tissue, root surface conditioning, and blood-clot stabilization under microscopic magnification, without flap elevation. Detailed materials, equipment, and procedural steps are described to support reproducibility. Two representative clinical applications are summarized, showing complete reduction of probing pocket depth and stable healing up to 10 months. This technique may serve as a reproducible, low-invasive alternative to conventional flap-based regenerative surgery for preservation of the maxillary canine teeth in dogs.